Finite-Time Distributed Cooperative Guidance Law with Impact Angle Constraint - Wenguang Zhang; Jin Yan (International Journal of Aerospace Engineering)
The problem of the distributed cooperative guidance law of multiple missiles attacking a stationary target with impact angle constraint is investigated. A distributed cooperative guidance law, which consists of a nonsingular terminal sliding mode component for ensuring finite time convergence to the desired LOS angle and a coordination component for realizing finite time consensus of time-to-go estimates, is proposed. Analysis shows that the guidance law designed in this study can ensure that missiles’ time-to-go estimates represent real times to go once all the missiles fly along the desired LOS. Therefore, simultaneous arrival can be guaranteed. Furthermore, it is modified to accommodate the communication failure cases. Compared with existing results, this guidance law owns faster convergence rate and can satisfy large impact angles. Numerical simulations are performed to demonstrate the effectiveness of the proposed guidance law.